Unpaid Work in Nursing Homes Flexible Boundaries - armstrong, Pat (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. The COVID-19 pandemic has made unpaid care more visible through its absence, while also increasing the need for it. Drawing on a range of research projects covering Canada, Germany, Norway, Sweden, the UK and the US, this book documents a broad spectrum of unpaid work performed by residents, relatives, volunteers and staff in nursing homes. It demonstrates how boundaries between paid and unpaid work are flexible, varying considerably with conditions, time, place and intersectional populations. By examining the complex labour process within nursing homes, this book provides insight and understanding which will be critical in planning for nursing home care post-pandemic.